Boosting hydrogen production from steam reforming of glycerol via constructing moderate metal-support interaction in Ni@Al2O3 catalyst. (15th September 2022) - Wang, Yunzhu; Zhu, Songshan; Lu, Jichang; Liu, Jiangping; Zhao, Yi; He, Sufang; Zhao, Yuhui; Lu, Huihui; Luo, Yongming
Graphical abstract: Highlights: Regulatory mechanism of nickel-alumina interaction on catalytic activity was elaborated. Ni@Al2 O3 with moderate nickel-alumina interaction exposed high active nickel surface areas. Ni@Al2 O3 with moderate nickel-alumina interaction achieved superior catalytic performance. Nickel-alumina interaction can affect the morphology and growth mechanism of coke deposition. Abstract: In this manuscript, the relationship between metal-support interaction and the catalytic performance for hydrogen production from steam reforming of glycerol (GSR) over Ni-Al2 O3 based catalysts was studied. Pure core–shell structured Ni@Al2 O3 and supported Ni/Al2 O3 with a fixed medium-sized nickel particle were synthesized without the other additional components to eliminate the influence of other factors. And then the nickel-alumina interaction of Ni@Al2 O3 was tuned precisely and the regulatory mechanism of nickel-alumina interaction on catalytic activity was elaborated. The strong nickel-alumina interaction over Ni/Al2 O3 and Ni@Al2 O3 with high calcination temperature resulted in the formation of NiAl2 O4, which was unfavorable to the reduction of nickel species to obtain the more active nickel. Consequently, the poor catalytic performance was caused. The moderate nickel-alumina interaction of Ni@Al2 O3 promoted the exposure of the maximum area of active nickel and obtained higher turnover frequency (TOF). Thus, Ni@Al2 O3 showed the high catalytic performance in GSR. Additionally, metal-support interaction affected the morphology and growth mechanism of coke deposition. For Ni@Al2 O3 with moderate nickel-alumina interaction, the formation of carbon deposition followed the 'tip-growth' pattern, and the filamentous coke was mainly formed on catalysts. Conversely, 'base-growth' pattern was followed on Ni/Al2 O3 with strong nickel-alumina interaction to form mainly encapsulated coke. The research findings of the regulatory role of interaction between nickel and alumina on catalytic performance will provide valuable guidelines for designing effective GSR catalysts.